(3cJGH CfhGQ GdBKGQ GdeNJUI HaVd GdUdGI Ydi GdfHi GdeNJGQs - (3CMeO Hf eYO Hf YjSi Hf hcjd GdJLjHj, GHf GdCbdjTj , CHh GdYHGS,J (B550 (3g` s
(3ChdgG (B:s
(3GSJNjQ Gddg GdhGMO Gdedc GdbgGQ HYO MeOg GdPi gh ef CfaS GdCPcGQ s
(3BNQgG (B:s
(3aQDi ai GdehVY GdPi cfG fJbGHd ajg YehO ef fhQ HdZ CYfGf GdSeGA abjd eG gPG GdfhQ abjd UdGJgeG Ydi QShd Gddg Udi Gddg Ydjg hSde ChTQa hcQe BNQ GdcJGH s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B259 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B181s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(155(3b(B) s
Keywords: (3GdMOjK h GdeUWdMs